Survival of a newborn from a pregnant woman with rabies infection - Zhen-Yu,Qu (2016)
Abstract Background Rabies is very common in People’s Republic of China. Each year thousands of people die because of this disease, but rabies diagnosed in pregnancy is very rare. Case Presentation In this study, we report the case of a pregnant woman who was infected with the rabies virus after a dog bite. The symptoms of rabies appeared in labor and she died after pregnancy. Her baby and husband did not develop the disease. Conclusion The phenomenon that the newborn infant was healthy may be related to the protective role of placenta in resisting the invasion of the rabies virus or the absence of systemic viremia. The prompt administration of vaccines and anti-rabies immunoglobulin to the infant may have also contributed to his survival.